2014
DOI: 10.1016/s0140-6736(14)61373-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of β blockers in patients with heart failure plus atrial fibrillation: an individual-patient data meta-analysis

Abstract: Menarini Farmaceutica Internazionale (administrative support grant).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
417
7
54

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 516 publications
(492 citation statements)
references
References 51 publications
14
417
7
54
Order By: Relevance
“…[97] In patients with LVEF <35% and mild symptoms (NYHA II), the addition of the aldosterone blocker eplerenone to an optimal HF regimen demonstrated further reduction in new onset AF (HR 0.58, P=0.034).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…[97] In patients with LVEF <35% and mild symptoms (NYHA II), the addition of the aldosterone blocker eplerenone to an optimal HF regimen demonstrated further reduction in new onset AF (HR 0.58, P=0.034).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…U pacjentów z AF często stwierdza się zmiany w istocie białej mózgu, zaburzenia czynności poznawczych [28][29][30], pogorszenie jakości życia [31,32] oraz obniżony nastrój [33], a każdego roku jest hospitalizowanych 10-40% pacjentów z AF [23,34,35]. Bezpośrednie koszty AF stanowią już w przybliżeniu 1% wszystkich wydatków na opiekę zdrowotną w Wielkiej Brytanii, a w Stanach Zjednoczonych w 2008 roku wyniosły 6-26 mld dolarów [36,37], co wynika z powikłań związanych z AF (np.…”
Section: Zgonunclassified
“…W skrócie u pacjentów z HFrEF nadają się do tego tylko beta-adrenolityki i digoksyna, ponieważ werapamil i diltiazem wywierają ujemne działanie inotropowe. Beta-adrenolityki są zwykle lekami pierwszego rzutu u pacjentów z klinicznie stabilną HFrEF, choć w metaanalizie indywidualnych danych pacjentów z randomizowanych, kontrolowanych prób klinicznych (RCT) nie stwierdzono, aby stosowanie beta-adrenolityków wiązało się ze zmniejszeniem umieralności w porównaniu z placebo u pacjentów z AF na początku obserwacji (HR 0,97; 95% CI 0,83-1,14) [23]. W praktyce klinicznej często przepisuje się digoksynę, ale nie przeprowadzono bezpośrednich porównawczych RCT u pacjentów z AF.…”
Section: Pacjenci Z Migotaniem Przedsionków Oraz Niewydolnością Sercaunclassified
See 1 more Smart Citation
“…As increased HR is associated with reduced survival in HF, it might be anticipated that the key mechanism leading to an excess of deaths in HF patients with concomitant AF is mainly due to increased ventricular rate, and that rate-limiting pharmacotherapy should improve the prognosis in those patients. However, hitherto studies have shown that in HF patients with concomitant AF: 1) ventricular rate of below 70 bpm is related to worse outcomes, and 2) treatment with beta-blockers has failed to reduce mortality and morbidity in patients with reduced LVEF [3,48,49]. There is no clear recommendation regarding either target HR or the use of beta-blockers in this population [3].…”
Section: Prognostic Factors In Different Heart Failure Subpopulationsmentioning
confidence: 99%